2002
DOI: 10.3141/1787-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle and Mix Characteristics on Performance of Some Granular Materials

Abstract: Three types of aggregate—a dolomitic limestone, a granodiorite, and a gravel—were studied to investigate the relationship between the particle properties and their performance in terms of strength, elastic behavior, and resistance to permanent deformation. Particles of each material were assessed for their geometry at both coarse and fine scales. This was quantified using several different measures including particle shape, roughness factor, roundness, sphericity, surface friction characteristics, and angulari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…Similar results were shown by Kandhal and Parker [5], that the HMA mixtures consisting of excessive flat and elongated aggregate particles tended to break down, affecting the mix durability. The fatigue performance of the asphalt mixture was also affected by the particles' roundness and angularity, concluded based on Cheung and Dawson's research [6]. In their studies, with the angularity increasing, the ultimate shear strength increased, and permanent deformation decreased, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…Similar results were shown by Kandhal and Parker [5], that the HMA mixtures consisting of excessive flat and elongated aggregate particles tended to break down, affecting the mix durability. The fatigue performance of the asphalt mixture was also affected by the particles' roundness and angularity, concluded based on Cheung and Dawson's research [6]. In their studies, with the angularity increasing, the ultimate shear strength increased, and permanent deformation decreased, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…From these test results, resilient and permanent deformation characteristic are analyzed so that a permanent deformation model is developed which can consider number of load repetition N, confining stress (σ 3 ), shear stress ratio(τ/τ f ) and stiffness of the material. 상관성이 있음이 지적되어 왔다 [9,10]. 또한 응력비 개념에 의 해 파괴시 축차응력에 대한 축차응력비(q/q f ) 또는 파괴시의 최대주응력에 대한 최소주응력비(σ 3 /σ 1 ) 및 재료의 전단강도 에 대한 전단응력의 비 즉, 전단응력비(τ/τ f ) 등이 영구변형의 발생에 중요한 영향을 미치는 변수로 지적된 바 있다 [8,11] (2) …”
Section: 서 론unclassified
“…Moreno and Rubio (2013) also concluded that the nature of coarse aggregate has an important effect in the fatigue-cracking life in asphalt mixes and should be considered in mix design. Cheung & Dawson (2002) agree that both angularity and the lack of it in the aggregates will have a strong impact on the performance of stiffness and permanent deformation, enhancing the performance of the mixture with the angularity of the particles. Regarding the shape, Kandhal & Parker (1998) indicated that the presence of elongated and flat particles affect the durability of the asphalt mixture because such particles tend to break during the mixing, laying and pavement service.…”
Section: Introductionmentioning
confidence: 96%